Integrated Methodology for the Optimization of Mine Closure - Kahnt, R; Paul, M (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
Following an introduction to the conceptual site model approach, examples of the application of this methodology to different mine closure problems are illustrated. Generally, under the large-scale WISMUT remediation project in Germany, the conceptual site model approach proved to be very powerful in assisting with decision analyses regarding the optimization of remedial measures. This is due to the fact that the water and contaminant load balance of the different mining objects (tailings facilities, piles, open pits, underground mines and processing plants) in particular, can be very effectively represented by flexible multi-compartment models. The software platform GoldSimTM is an ideal tool for the required iterative approach. Additionally, applications of the conceptual site model approach described in this paper illustrate that meaningful results can be achieved with a multi-compartment approximation using limited data, even for a complex remedial problem.